Application and evaluation of short-term emergency ratings for double-circuit transmission lines - Kim, S. D.; Kim, S. R.; Morcos, Medhat M. (My University, 2012)
Emergency ratings have been introduced for operating transmission lines safely and supplying current capacity efficiently, as well as controlling load flow when occurring line faults. In this paper, short-term emergency ratings are calculated by using thermal equilibrium equation for bared conductors in double-circuit transmission lines. Overhead transmission lines installed in double-circuit have been extensively utilized worldwide to enhance power transmission. Such lines show various advantages in increasing transmission capacity and decreasing power loss as well as being operated flexibly during a contingency. Even when a fault occurs in one circuit, the healthy circuit can supply power continuously during emergency without outage. The utilization of such double-circuit transmission lines during normal and/or emergency operations is described. Maximum normal operating current based on fault duration, maximum allowable temperature of conductor, and thermal line ratings are evaluated. Several performances of dip/clearance affecting short-term emergency rating are also presented.
Keywords: Double-circuit transmission lines; Short-term emergency rating; Thermal line rating